Chapter La rivoluzione del lavoro moderno - Seghezzi, Francesco (Firenze University Press, 2025)
The chapter introduces the section of the volume that deals with the historical period from the first beginnins of the industrial revolution to its most mature phase (Fordism) up to just before its crisis. It analyses the various aspects of it, starting with the emergence of the social question and the new role that work began to have at the rise of industrial capitalism. It is then illustrated how it is possible to speak, from the point of view of labour, of a Fordist compromise starting from the first decades of the 20th century. Other aspects concern the relationship between psychology and work, but also the beginning of important reflections on the meaning of work itself, in its relationship with fatigue but also with redemption. The contribution addresses how the relationship between work and idleness evolved in the context of the early 20th century.